Analisis Kondisi Isolasi Pada Station Service Transformer (SST) - Rachmat Sutjipto; Harrij Mukti K; Kharisma Eka Dzulfiqar (Elposys: Jurnal Sistem Kelistrikan, 2024)
There is an identified oil leak in SST Unit 1 at Paiton Power Plant, discovered after a fault indicator in Central Control Room. Visual inspection revealed that the gasket seal on the fastening bolts was damaged due to the seal reaching its lifetime limit. Continuous oil leaks degrade the transformer's oil, reducing its volume and impairing the transformer's cooling performance. The research aims to evaluate the insulation condition of the SST transformer before and after replacing the damaged gasket seal (repacking). This evaluation ensures the transformer's optimal performance and reliability by preventing potential failures caused by degraded insulation. The research employs a quantitative approach, using various tests to assess the insulation resistance of the transformer, including the Polarization Index (PI), Tangent Delta, and Breakdown Voltage tests. Data were collected from technical assessments and measurements conducted on-site at PT. PLN Nusantara Power (PLN NP). The comparison of data before and after repacking indicated significant improvements in the insulation condition of the SST transformer. All test results—PI, Tangent Delta, and Breakdown Voltage—met the standards post-repacking, showing better performance than before. Specifically, the Polarization Index and Tangent Delta values improved substantially, aligning with the IEEE C57.152-2013 standard, and the Breakdown Voltage met the IEC 60156-95 standard. The findings suggest that timely maintenance, such as gasket seal replacement, is crucial for maintaining the insulation quality and overall performance of transformers. Regular inspections and adherence to testing standards can prevent operational failures and extend the lifespan of critical electrical equipment.